Malicious software prevention for Muslim communities - Ahmad Zabidi, Muhammad Najmi (s.n, 2012)
Malicious software or popularly known as malware is a threat to the computer users, regardless which platform that they are using; desktops, laptops or mobile phones. Malware is a type of software which purposely written for malicious purpose. It manipulates software vulnerability to get illegal access to the host machine. Malware evolves from a primitive, straight forward software to sophisticated and difficult to detect features, for instance by using decryptors, obfuscations and packers.